Local Wisdom of the Lasem Community for Tolerance (Forum Ilmu Sosial, 2022)
Despite the widespread issue of intolerance in Indonesia, some regions can implement a harmonious life based on the values of Pancasila and Bhineka Tunggal Ika. The area is Lasem City, Rembang Regency, which consists of a multicultural community of Javanese and Chinese ethnicities. Tolerance in the multicultural Lasem community has existed since ancient times. Diverse life in Lasem develops harmoniously with empathy based on local cultural values. Local culture with messages of local wisdom based on the community is necessary for a harmonious life in a multicultural society. This study aims to analyze the local wisdom of the Lasem community for harmonizing religious life. This research is qualitative research with a case study method. Data were collected using observation, interviews, and documentation. Data analysis was performed using interactive analysis techniques: data reduction, data presentation, and conclusion drawing. The study results show that tolerance among Lasem people is intertwined in various aspects of life, religious life, social life, economy, politics, and culture. The local wisdom of the Lasem people is an important foundation for the community to create a harmonious life. The local wisdom that forms the basis of tolerance in Lasem includes historical stories of Lasem and teachings of Javanese-Islamic and Chinese-Confucian cultures. The values of local wisdom are proven to have a strategic role in harmonizing religious life in the Lasem community. The role of community leaders such as religious leaders and local government also holds a very high urgency in providing examples and advice related to local wisdom, always to be internalized and upheld by the community. The existence of local wisdom must always be preserved in modern society. To realize this, the role of stakeholders such as the government and community leaders is very important to work hand in hand so that local wisdom can continue to become the roots and philosophy of life for the community.